2003
DOI: 10.1891/rtnp.17.2.137.53173
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of the Family Caregivers’ Role: A Qualitative Study

Abstract: In Ireland, there is a dearth of research exploring the perceived health and social care needs and experiences of family caregivers of older people. In response, this research study was conducted to explore the profile, role and needs of family caregivers as a means of understanding their experience of caring. The study also set out to identify coping strategies employed by caregivers and explore positive aspects of the caring relationship in relation to quality of life, information needs, day care and respite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 19 publications
5
67
0
10
Order By: Relevance
“…Lane et al [30] even argued in favour of integrating respite care provision with health care planning. Yet, for the development of client-centred, effective and efficient respite care programmes, knowledge of needs, desires and use of respite is crucial [31].…”
Section: Effectiveness Of Respite Carementioning
confidence: 99%
“…Lane et al [30] even argued in favour of integrating respite care provision with health care planning. Yet, for the development of client-centred, effective and efficient respite care programmes, knowledge of needs, desires and use of respite is crucial [31].…”
Section: Effectiveness Of Respite Carementioning
confidence: 99%
“…Lane et al (2003) and Milliken and Northcott (2003) found that the family caregiver was the most significant person for enhancing wellness of a person with this disease. Current studies relating to family caregivers are focused on the needs of family caregivers in caring for their ill members (Chien & Norman, 2003;Subgranon & Lund, 2000;Yamamoto & Wallhagen, 1998).…”
mentioning
confidence: 99%
“…The aspect that seems to generate the fear is a possible confrontation with a patient suffering from cancer that in a way relates to them through family or social connections. Assuming the role of the caregiver in these situations can be burdensome and often can lead to excess stress, disempowerment and lack of effectiveness in their role [25,26]. The cultural aspect of cancer as a taboo should also be considered in these situations since largely cancer is connected to death and dying [18].…”
Section: Resultsmentioning
confidence: 99%